Phenotyping of nNOS neurons in the postnatal and adult female mouse hypothalamus - Chachlaki, K; Malone, SA; Qualls-Creekmore, E; Hrabovszky, E; Münzberg, H; Giacobini, P; Ango, F; Prevot, V (Wiley, 2017)
Neurons expressing nitric oxide (NO) synthase (nNOS) and thus capable of synthesizing NO play major roles in many aspects of brain function. While the heterogeneity of nNOS-expressing neurons has been studied in various brain regions, their phenotype in the hypothalamus remains largely unknown. Here we examined the distribution of cells expressing nNOS in the postnatal and adult female mouse hypothalamus using immunohistochemistry. In both adults and neonates, nNOS was largely restricted to regions of the hypothalamus involved in the control of bodily functions, such as energy balance and reproduction. Labeled cells were found in the paraventricular, ventromedial, and dorsomedial nuclei as well as in the lateral area of the hypothalamus. Intriguingly, nNOS was seen only after the second week of life in the arcuate nucleus of the hypothalamus (ARH). The most dense and heavily labeled population of cells was found in the organum vasculosum laminae terminalis (OV) and the median preoptic nucleus (MEPO), where most of the somata of the neuroendocrine neurons releasing GnRH and controlling reproduction are located. A great proportion of nNOS-immunoreactive neurons in the OV/MEPO and ARH were seen to express estrogen receptor (ER) α. Notably, almost all ERα-immunoreactive cells of the OV/MEPO also expressed nNOS. Moreover, the use of EYFPVglut2 , EYFPVgat , and GFPGad67 transgenic mouse lines revealed that, like GnRH neurons, most hypothalamic nNOS neurons have a glutamatergic phenotype, except for nNOS neurons of the ARH, which are GABAergic. Altogether, these observations are consistent with the proposed role of nNOS neurons in physiological processes.